A rare case report of traumatic phacocele - Kochar, Rashi; Ahuja, Nisha; Agarwalla, Vijaya; Dhore, Nilay (International Journal of Research in Medical Sciences, 2023)
A 67-year-old woman visited our facility and complained of right eye pain, redness, and sudden loss of vision. There was history of blunt trauma to right eye by goat horn 25 days before. Visual acuity of light perception was present in right eye. On slit lamp examination, right eye revealed a clearly defined mass in subconjunctival space close to the limbus with scleral rupture. Anterior chamber was irregular in depth with vitreous stands in anterior chamber. Clinically there was aphakia. The patient was diagnosed with right eye traumatic phacocele and scheduled for surgical excision of the crystalline lens with scleral wound repair. A blunt injury may cause an indirect scleral rupture, which would then cause the crystalline lens to dislocate in the subtenon or subconjunctival area. Phacocele, a rare ocular manifestation of blunt trauma caused by indirect scleral rupture of the globe, is one of a number of ocular manifestations of blunt trauma. In this case, the cataractous lens was dislocated in the subconjunctival space due to indirect trauma from a goat horn, without any precipitating conditions.